How an e-Learning Course Was Created to Support Primary Teachers’ Facilitation of Student Reflective Practice through Educational Vlogging - Molloy Ken; Crotty Yvonne (International Journal for Transformative Research)
This article explains how teachers can use educational vlogging as a tool to facilitate students’ reflective practice in primary schools. Vlogging is a short duration video recording that engages the learner in critical self-reflection. The widespread accessibility of digital devices in Irish schools offer primary teachers opportunities to use vlogging as a tool to enable students to reflect on their learning, and gather learning analytics that provide insight into the learning process. The Educational Entrepreneurial Approach (EEA) (Crotty, 2014) to action research was employed to show how examining a Covid-19 school news broadcasting project provided the rationale for developing and creating an e-learning course. This course consisted of fifteen educational videos that aimed to enable teachers to facilitate student vlogging in a disadvantaged primary school. Research data was gathered through reflective journaling and validated through meetings between me as researcher (Author 1), my Supervisor (Author 2), and fellow students on the MSc. in Education and Training Management (eLearning) colleagues – hereafter referred to as MEME. Findings offer insights into the benefits and limitations of educational vlogging and detail how creating the e-learning course, Vlogging in the Primary School, was transformative for me and for the school. The outcomes indicate that educational vlogging can potentially benefit teachers and students in Irish primary schools and beyond.